Penerapan Metode Pieces Framework Sebagai Evaluasi Tingkat Kepuasan Pengguna Aplikasi Seabank di Balikpapan - Nurhalisa Sakir; Joy Nashar Utama Jaya; Nuorma Wahyuni (JURIKOM (Jurnal Riset Komputer), 2022)
SeaBank is a digital banking application that helps the people of Balikpapan carry out financial activities ranging from saving to payments anytime, anywhere via mobile phones. SeaBank's first product was a savings account. This makes it easy to manage your daily financial activities and provides savings in accounts with high interest rates. The SeaBank application can be installed on smartphones such as Android and iOS. Just connect to the internet and access SeaBank and you are ready in minutes. The SeaBank application has many menus, including: The SeaBank application needs to identify problems to find out how satisfied users are with the SeaBank application. One of the evaluation methods is the PIECES method (performance, information, economy, control, efficiency, service). You can determine user satisfaction for each domain based on the PIECES method, which consists of performance, information, economy, control, efficiency, and service in measuring user satisfaction for SeaBank applications. Equal performance. A value of 4.36 receives a value of 4.28, the economy receives a value of 4.35, controlling a value of 4.34, streamlining a value of 4.31 and services of a value of 4.22. So that the average value obtained is 4.31, it can be categorized as satisfied users. The SeaBank application plays a big role in increasing user satisfaction for the SeaBank application and provides satisfaction and positive feedback to application users